2022
DOI: 10.1007/s42106-022-00216-1
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Sowing Time and Conservation Tillage - The Climate-Resilient Approach to Enhance the Productivity and Profitability of Wheat

Abstract: Field experiments consisting of two sowing time (early and timely), two tillage options (conventional tillage and conservation tillage) and ten genotypes were conducted with the aim to maximize the wheat productivity and profitability. The early sowing (second fortnight of October) produced 16.0% higher grain yield compared to timely sowing (mid-November) in northern Indian Plains. However, no significant yield differences were observed between conventional tillage (CT) and conservation tillage (CST) practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Conservation tillage was observed to increase wheat grain yield by 10–20% compared to conventional tillage 56 , 57 , which can be attributed to improved soil health and maintained soil moisture in the root zone, providing a better environment for wheat growth and development. An important advantage of conservation tillage is the reduction of production costs by US $33 to 50 58 – 60 , including the need for labor and fuel used in tillage operations and equipment maintenance. Among conservation tillage practices, zero tillage for wheat production was found to be most successful in terms of good crop establishment and increased yield 61 – 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Conservation tillage was observed to increase wheat grain yield by 10–20% compared to conventional tillage 56 , 57 , which can be attributed to improved soil health and maintained soil moisture in the root zone, providing a better environment for wheat growth and development. An important advantage of conservation tillage is the reduction of production costs by US $33 to 50 58 – 60 , including the need for labor and fuel used in tillage operations and equipment maintenance. Among conservation tillage practices, zero tillage for wheat production was found to be most successful in terms of good crop establishment and increased yield 61 – 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Drought is one of the major abiotic stresses that cause significant reductions in crop yield and quality [1,2] and is expected to be more severe since the occurrence of drought is increased due to alteration in the evapotranspiration (ET) as well as unfavorable rainfall distribution caused by global warming [3,4]. Several study results have shown that the negative consequences of drought can be overcome by adaptation of different strategies to improve the climate resilience of agriculture, i.e., sowing time [5][6][7], tillage systems [8,9], irrigation [10][11][12], selection of crop and varieties [13,14] and use of beneficial soil bacteria and mycorrhizal fungi [15,16]. The latter was reported in the literature as a complementary measure that can mitigate the effects of biotic and abiotic stresses in crop production [16].…”
Section: Introductionmentioning
confidence: 99%